Innovative method by design-around concepts with integrating the algorithm for inventive problem solving - Chen, Wang-Chih; Chen, Jahau Lewis (Journal of mechanical science and technology, 2014)
The work proposes a new design tool that integrates design-around concepts with the algorithm for inventive problem solving (Russian acronym: ARIZ). ARIZ includes a complete procedure for analyzing problems and related resource, resolving conflicts and generating solutions. The combination of ARIZ and design-around concepts and understanding identified principles that govern patent infringements can prevent patent infringements whenever designers innovate, greatly reducing the cost and time associated with the product design stage. The presented tool is developed from an engineering perspective rather than a legal perspective, and so can help designers easily to prevent patent infringements and succeed in innovating by designing around. An example is used to demonstrate the proposed method.